Posttranscriptional regulation of smoothened is part of a self-correcting mechanism in the Hedgehog signaling system. - Alcedo, J.; Zou, Y.; Noll, M. (Molecular Cell, 2000)
Hedgehog signaling, mediated through its Patched-Smoothened receptor complex, is essential for pattern formation in animal development. Activating mutations within Smoothened have been associated with basal cell carcinoma, suggesting that smoothened is a protooncogene. Thus, regulation of Smoothened levels might be critical for normal development. We show that Smoothened protein levels in Drosophila embryos are regulated posttranscriptionally by a mechanism dependent on Hedgehog signaling but not on its nuclear effector Cubitus interruptus. Hedgehog signaling upregulates Smoothened levels, which are otherwise downregulated by Patched. Demonstrating properties of a self-correcting system, the Hedgehog signaling pathway adjusts the concentrations of Smoothened and Patched to each other and to that of the Hedgehog signal, which ensures that activation of Hedgehog target genes by Smoothened signaling becomes strictly dependent on Hedgehog.